COVID-19 Related Fears Among Mzuzu University’s Nursing Students During Clinical Practice - Mpasa F; Baluwa M; Lungu F; Chipeta MC; Munthali G; Mhango L; Chimbe E; Konyani A (Dove Medical Press, 2021)
Ferestas Mpasa, Masumbuko Baluwa, Florence Lungu, Mep Coretta Chipeta, Getrude Munthali, Lucky Mhango, Ettah Chimbe, Alice Konyani Department of Nursing and Midwifery, Mzuzu University, Mzuzu, 2, MalawiCorrespondence: Ferestas MpasaMzuzu University, Department of Nursing and Midwifery, Private Bag 201, Luwinga, Mzuzu, 2, MalawiTel +265 888317160Fax +265 1 320568Email mpasa.f@mzuni.ac.mwPurpose: Clinical practice during pandemics is known to bring additional fears to nursing students. The purpose of this study was to explore fears of Mzuzu University's nursing students nurses regarding resumption of clinical practice amidst the Coronavirus disease (COVID-19) pandemic.Methods: The study used a qualitative approach employing a descriptive phenomenological design. Mzuzu University Research Ethics Committee (MZUNIREC) approved the study and issued MZUNIREC/DOR/20/06 as approval number. An independent person collected data through four focus group discussions with a purposefully selected sample of 40 consented nursing students who had completed clinical practice during the first wave of the COVID-19 pandemic. Data analysis was done manually using content analysis. The analysis started with transcription of the interviews. Following this, data were coded and categorized into themes and subthemes were established from participants' significant statements.Results: Four major themes about the fears amongst the student nurses emerged. These were as follows: equipment and supplies; increased perceived risk for acquiring and transmitting COVID-19; stigma and discrimination and perceived fear of not having adequate learning.Conclusion: Clinical practice during the COVID-19 pandemic brings fear among nursing students and requires that implementers of nursing and midwifery programs prioritize ascertaining student's skill, emotional wellbeing and provision of adequate resources before deploying them to clinical areas.Keywords: fears, student nurses, clinical experience, Corona virus disease, COVID-19